Coaches and Teammates as Social Agents for Collegiate Athletes’ Basic Psychological Need Satisfaction - Raabe, Johannes; Zakrajsek, Rebecca A. (Journal of Intercollegiate Sport, 2017)
Teammates and coaches might be considered two of the most significant sources of social interactions for athletes. Deci and Ryan’s (2000) self-determination theory offers a motivational framework that can be used to understand the quality of relationships within sport. Given the positive outcomes associated with fostering basic psychological need satisfaction (e.g., optimal social functioning, well-being, and self-development) researchers have been interested in understanding how athletes’ perceptions of competence, autonomy, and relatedness can be nurtured. The purpose of the current study was to assess: (a) if there was a difference between participants’ perceptions of their coaches’ and teammates’ influence on their basic psychological need satisfaction, (b) potential differences between participants’ perceptions regarding the impact of coaches and teammates on their basic psychological need satisfaction in interactive and coactive sports, and (c) whether coaches’ and teammates’ influence on athletes’ basic psychological need fulfillment affected participants’ perception of, and satisfaction with, individual and team performance. 362 National Collegiate Athletic Association Division I student-athletes (226 female and 136 male; Mage = 19.36; SD = 2.65) from four different sports (i.e., track and field/cross country, soccer, basketball, and tennis) participated in the study. Results showed that while peers had a significantly more positive influence on individuals’ basic psychological need satisfaction than coaches, it was the need fulfillment from coaches that predicted athletes’ perceptions of, and satisfaction with, performance.